Kontribusi Program Tol Laut Rute T19 dalam Mendukung Merauke sebagai Lumbung Pangan Nasional - Widiastuti, Maria Maghdalena Diana; Syaukat, Yusman; Falatehan, Falatehan; Hakim, Dedi Budiman (AGRICOLA, 2022)
The sea highway program aims to connect the western and eastern parts of Indonesia and reduce price disparities. The implementation began in December 2020 using ship namely Logistik Nusantara 2 with route from Merauke-Pomako-Kokas-Sorong-Korido-Merauke. The capacity of T19 is 1500 tons with revolving for one month. The purpose of this study is to evaluate the implementation of sea highway program route T19 in supporting the Merauke food estate program. Methodology used qualitative through literature study and verification primary data with interviewed the stakeholders. The results showed that the main cargo from Merauke is rice as market demand from Jayapura, Timika and Sorong. The shipload return to Merauke is chipped rock, sand, and rock ash. The differences of distribution cost is Rp. 150/kg when compared to private shipping. However, the loading capacity is relatively low, on average, 33.46% are filled, while the return load is 10.47%. The conclusion, sea highway program for the T19 route is an important vehicle in the distribution and marketing process of rice, especially for distributing rice from surplus to deficit areas. The contribution is very important in developing the food estate program, but it is necessary to optimalization of these transportation to fullfill the load target.